2007
DOI: 10.1302/0301-620x.89b3.18146
|View full text |Cite
|
Sign up to set email alerts
|

Subtrochanteric insufficiency fractures in patients on alendronate therapy

Abstract: We carried out a retrospective review over ten months of patients who had presented with a low-energy subtrochanteric fracture. We identified 13 women of whom nine were on long-term alendronate therapy and four were not. The patients treated with alendronate were younger, with a mean age of 66.9 years (55 to 82) vs 80.3 years (64 to 92) and were more socially active. The fractures sustained by the patients in the alendronate group were mainly at the femoral metaphyseal-diaphyseal junction and many had occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
350
4
18

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 450 publications
(390 citation statements)
references
References 17 publications
18
350
4
18
Order By: Relevance
“…(10)(11)(12)(13) A relatively large proportion of patients also has taken GCs in addition to BPs. GCs reduce osteoblast activity, increase osteoblast apoptosis, (14)(15)(16) and are also associated with osteonecrosis of the femoral head.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
See 3 more Smart Citations
“…(10)(11)(12)(13) A relatively large proportion of patients also has taken GCs in addition to BPs. GCs reduce osteoblast activity, increase osteoblast apoptosis, (14)(15)(16) and are also associated with osteonecrosis of the femoral head.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
“…The bone marrow was hypercellular, but there was no evidence of inflammation, malignancy, or myelosclerosis. Goh and colleagues (10) performed qualitative histology on biopsies removed intraoperatively during repair of subtrochanteric fractures in 5 alendronate-treated patients, but they simply reported that there was no evidence of neoplasia.…”
Section: Atypical Subtrochanteric and Femoral Shaft Fractures: Clinicmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in these fractures has increased recently, as many reports have been published suggesting that the distinction between typical and atypical fractures may be related to long-term bisphosphonate use. (1)(2)(3)(4)(5)(6)(7)(8) However, the increased risk of ST/FS fractures in patients taking bisphosphonates long term has not been clearly established and might be related to fragility fractures. (9)(10)(11)(12) Although the incidence of hip fractures has been well characterized, the incidence of ST/FS fractures has only recently been reported.…”
Section: Introductionmentioning
confidence: 99%